PENGARUH KONSENTRASI DAN LAMA PERENDAMAN DALAM LARUTAN KAPUR SIRIH TERHADAP MUTU KERIPIK PISANG KEPOK (Musa paradisiaca formatypica) - Afe Dwiani; Suburi Rahman (Universitas Muhammadiyah Mataram, 2021)
This research aimed to determine the effect of concentration and soaking time in calcium hydroxide (Ca(OH)2) on the quality of plantain chips (Musa paradisiaca formatypica). The method that used in this study was complete randomized design (CRD) with a double factors that was concentration of calcium hydroxide (1%, 5% and 10%) and soaking time (10, 20 and 30 minutes), with treatment are KP1 (1% : 10 minutes), KP2 (5% : 10 minutes), KP3 (10% : 10 minutes), KP4 (1% : 20 minutes), KP5 (5% : 20 minutes), KP6 (10% : 20 minutes), KP7 (1% : 30 minutes), KP8 (5% : 30 minutes) and KP9 (10% : 30 minutes). The data of the research were analyzed using Analysis of Variance at level 5% and tested continued using the test of Least Significant Different (LSD) at the same level if there was a real difference. The results showed that the concentration and soaking time in calcium hydroxide had a real effect on chemical qualities (water, ash, fat, and zinc/Zn) and organoleptic (taste, color, aroma, and texture) of plantain chips. In zinc content for all instruments are suitable with standard (SNI No. 01-4315-1996) for banana chips, while for moisture, ash, and fat content, not all treatments are suitable with the standard. In organoleptic parameters for taste, color, and aroma, panelists preferred treatment of KP1 (concentration of calcium hydroxide 1% and soaking time of 10 minutes) for best result, while for texture the treatment of KP9 (concentration of calcium hydroxide 10% and soaking time 30 minutes) produces the best quality based from panelist choice.